Evaluations of an entrepreneurship development program: A systematic literature review - Ronal Ferdilan; Wawan Dhewanto; Sonny Rustiadi (University of Islam Malang, 2021)
The contribution of entrepreneurship at both the microeconomic and macroeconomic levels is remarkable. There are many entrepreneurship development programs (EDP) initiatives proposed by policymakers around the world to ensure the growth of entrepreneurs. While EDP is necessary to improve entrepreneur capabilities, however studies on EDP evaluation literacy remain limited. This study aims to fill the gap by investigating EDP evaluation literacy by using a systematic literature review (SLR). This study carried out a bibliometric analysis on a Scopus database in the last three decades, from 1989 to 2021 with all the manuscripts were written in English. The results show that most of the literature on EDP evaluation-related themes is mainly focused on program evaluation, characteristics, challenges, stakeholders, and context, with program evaluation and characteristics are considered as the most significant issues of EDP evaluation. Interestingly, this study also reveals that few manuscripts review the process of EDP as the success criterion of EDP implementation.